Error Analysis on the Use of Part of Speech in Students’ Essay Writing at Secondary School EFL Classroom - Satria Mahardhika Rubiyanto (Retain: Journal of Research in English Language Teaching, 2024)
English is a crucial foreign language in Indonesia, and its learning and acquisition have become a popular topic in education. This study focuses on essay writing, which is a complex task that requires students to elaborate on specific topics and use their knowledge acquired in the classroom. Part of speech refers to the grammatical category of words used to form sentences, and understanding these parts helps writers construct sentences with clarity and precision. This study has objectives of (1) identifying the errors related to the use of different parts of speech which are most prevalent in students' essay writing in a secondary school EFL classroom; and (2) describing the underlying factors contributing to the errors the use of the parts of speech. This study is conducted using descriptive qualitative that is focused in analyzing errors found within the utilization of part of speech as well as investigating factors that contributes the errors committed by students in their essay writings. Six 11th grader students were participating in this research writing argumentative essays. The findings show that most of the students have reasonable proficiency in their writings, however there are several errors still present in their essays. The students claim a range of causes of the errors from rushing their work up to unawareness of said errors they committed.